Potential predictors of surgical evacuation following early medical abortion: a prospective study - Bansal, Ritu; Chaudhary, Naimaa K.; Sharma, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Medical management is the safer, effective and more convenient method for the management of missed abortion. Owing to the risk and complications, medical management is offered to all the women presenting with missed abortions. Yet after all possible efforts a large number of patients land up into surgical evacuation. This study is conducted for the in-depth analysis of the patient’s presenting complaints and their risk factors to establish the correlation of these factors with failed medical abortion. This would help in the establishment of easily identifiable subgroups for whom medical management would be a success. Methods: This is a prospective observational study conducted at St. Stephen’s hospital Delhi during September 2019-June 2020. 55 women with missed abortion attending the gynaecological clinic and emergency, were recruited based on inclusion and exclusion criteria. After taking informed and written consent, all cases were administered misoprostol by vaginal route for medical management. Patients were followed up for 24 hours and looked for the outcome. Results: We found that multiparity, advanced gestational age and previous caesarean deliveries were the predictors of uterine evacuation following failed medical management. Higher chances of complete abortion were seen among multiparous and among the patients who had bleeding at the time of presentation. Failure of medical management was seen in around 70% cases with more than 9 weeks gestational age. Lesser side effects are observed with 400 mcg misoprostol dosing. Conclusions: Nulliparous patients and the patients presenting with bleeding at the time of presentation had more complete abortion. Multiparity and previous caesarean delivery is associated with failed medical management. After studying the potential risk factors, every patient can be counselled about the chances of completion of medical management.